Innovative Solar Energy Applications in Agriculture and Water Management - Nishant Varshney (International Journal of Environmental Noise and Pollution Control, 2024)
Considering solar energy technologies have the potential to address issues with energy sustainability and water resources, their integration in agricultural and water management has received a lot of attention. This paper offers a thorough analysis of creative uses of solar energy in different fields, emphasizing developments in technology, advantages, difficulties, and potential applications. sun photovoltaics (PV), concentrated sun power (CSP), solar desalination technologies, and solar water pumping systems are all covered in this overview. Global case studies and examples show the economic, environmental, and social implications of practical implementations and outcomes. The study also addresses regulatory factors, financial incentives, and policy frameworks that affect the use of solar energy solutions in water management and agriculture.
Keywords: Global; Sun photovoltaics; concentrated sun power; multi-effect distillation; water management